Elemental composition of plankton exometabolites (mucous macroaggregates): Control by biogenic and lithogenic components - Kovač, Nives; Viers, Jérôme; Faganeli, Jadran; Bajt, Oliver; Pokrovsky, Oleg S. (Metabolites)
Among the various exometabolitic effects of marine microorganisms, massive mucilage events in the coastal zones of temperate and tropical seas are the most spectacular and environmentally important. Abundant mucilage material in the form of aggregates appears in late spring/early summer in the water column of the Adriatic Sea. These macroaggregate biopolymers originate mainly from plankton exometabolites, with both autochthonous and allochthonous components, and strongly impact the tourism, fisheries, and economy of coastal countries. In contrast to extensive studies on the structural and chemical nature of macroaggregates performed over past decades, the full elemental composition of these substances remains poorly known, which does not allow for a complete understanding of their origin, evolution, and necessary remediation measures. Here, we report the results of comprehensive analyses of 55 major and trace elements in the composition of macro aggregates collected at the surface and in the water column during massive mucilage events. Through normalization of the elemental chemical composition of the upper earth crust (UCC), river suspended material (RSM), mean oceanic plankton, and mean oceanic particulate suspended material, we demonstrate that the water column macroaggregates reflect a superposition of the signal from plankton and marine particulate matter. The surface macroaggregates were preferentially enriched in lithogenic component, and carried the signature of planktonic material. The rare earth element (REE) signal was strongly dominated by plankton and, to a lesser degree, by oceanic particulate matter, while at the same time being strongly (>80 times) impoverished compared with UCC and RSM. Taken together, the elemental composition of macroaggregates allows for distinguishing the lithogenic and biogenic impacts on the occurrence of these unique large-scale mucilage events, linked to the exometabolism of marine plankton combined with the input of allochthonous inorganic material.